Factors Influencing Pedestrian Movement in Banda Aceh: The Role of Urban Density, Land Use, and Connectivity - Naufal, Ghaffari; Yori Herwangi (Civil and Sustainable Urban Engineering, 2025)
High urbanization in Indonesia created significant mobility challenges, particularly due to the intensive use of motorized vehicles that led to congestion and environmental degradation. This study aimed to analyze the factors influencing pedestrian volume in Banda Aceh as an alternative solution to promote active mobility. The analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with three main variables—land use mix, density, and connectivity—measured across 44 grids of 800×800 meters within the city. The findings showed that density had a significant positive effect on pedestrian volume (path coefficient = 0.425; p-value = 0.007), while land use mix and connectivity did not demonstrate significant effects. The proposed model explained 27.2% of the variation in walking mobility. These results highlighted the importance of urban density in encouraging walking activity and suggested that compact urban development could be an effective strategy to promote active mobility in Indonesian cities.